MOCHA 2017 as a Challenge for Virtuoso - Spasić, Mirko; Jovanovik, Milos (Springer International Publishing, 2017)
The Mighty Storage Challenge (MOCHA) aims to test the performance of solutions for SPARQL processing, in several aspects relevant for modern Linked Data applications. Virtuoso, by OpenLink Software, is a modern enterprise-grade solution for data access, integration, and relational database management, which provides a scalable RDF Quad Store. In this paper, we present a short overview of Virtuoso with a focus on RDF triple storage and SPARQL query execution. Furthermore, we showcase the final results of the MOCHA 2017 challenge and its tasks, along with a comparison between the performance of our system and the other participating systems.
Keywords: Virtuoso; Social Network Benchmark; Benchmarking; Mighty Storage Challenge; MOCHA; Data Storage; Linked Data; RDF; SPARQL